옥탄가 변화에 따른 가솔린의 발화특성에 관한 연구 - 김형석; Hyeong Seok Kim; 김원길; Won Kil Kim; 최유정; Yu Jung Choi; 김정훈; Jung-hun Kim; 최재욱; Jae-wook Choi (한국안전학회지, 2018)
This study was conducted to assess the hazards of gasoline in relevance to the changes in octane numbers, and gasoline’s spontaneous ignition temperature and instantaneous ignition temperature were measured. Spontaneous ignition temperature of regular gasoline was 301℃ for sample quantity of 100∼125 ㎕. Spontaneous ignition temperature of middle gasoline was 380℃ for sample quantity of 125 ㎕ and that of premium gasoline was 400℃. As gasoline’s octane numbers increased, their spontaneous ignition temperatures increased, and their instantaneous ignition temperature were almost identically 499℃ for sample quantity of 125 ㎕. In addition, activation energies of regular gasoline, middle gasoline, and premium gasoline were 10.48 Kcal/mol, 16.89 Kcal/mol, and 24.55 Kcal/mol respectively.